2008
DOI: 10.1007/s00128-008-9516-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elevated CO2 and O3 on Phenolic Compounds in Spring Wheat and Maize Leaves

Abstract: C(3) crops are generally considered more sensitive than C(4) crops to the elevated CO(2) and O(3), but it is unclear whether the concentrations of phenolic compounds in them are affected. In this paper, an enrichment experiment with open-top chamber was conducted to examine the effects of elevated CO(2), O(3), and their combination on the contents of total phenolic compounds and flavone in the leaves of spring wheat (C(3) crop) and maize (C(4) crop). The results showed for spring wheat, the total phenolic cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…This is attributed to the amount of substrate available to biosynthesise of phenolic compounds (Bustos, Riegel & Calderini, 2012). Phenolic content was not affected by annual ryegrass competition at both well-watered and drought conditions under e[CO 2 ], in agreement with previous research on phenolic content of wheat leaves (Li, Shi & Chen, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…This is attributed to the amount of substrate available to biosynthesise of phenolic compounds (Bustos, Riegel & Calderini, 2012). Phenolic content was not affected by annual ryegrass competition at both well-watered and drought conditions under e[CO 2 ], in agreement with previous research on phenolic content of wheat leaves (Li, Shi & Chen, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…The enrichment with [CO 2 ] may differentially affect the content of phenolic compounds in cereal leaves. Li et al observed an increase in total phenolics of wheat and maize leaves at e­[CO 2 ] during both the vegetative and the ripening stage. As far as antioxidants of rice grains are concerned, both free and bound phenolic compounds were negatively affected by e­[CO 2 ] .…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of increases in phenolic compounds in response to increased atmospheric O 3 , as in the case of red clover (Trifolium pratense L.), whose total phenolic compounds increased between 5 and 12% with concentrations of 0.038 and 0.056 mg•L −1 of O 3 (range 1.26 times above ambient O 3 ) [59]. In wheat (Triticum aestivum L.) exposed to 0.384 mg•L −1 of O 3 , an increase in phenol content was also observed; however, this increase depended on the phenological stage of the crop, being higher at the grainfilling stage than during vegetative growth [60]. In another study of red lettuce grown under artificial light, the total phenolics, flavonoids, and anthocyanins showed a significant increase after 0.25 h of exposition on the fourth leaf [61].…”
Section: Total Phenol Contentmentioning
confidence: 97%